Auditor Seniority, Auditor Experience and Auditor Expertise towards Professional Judgment With Locus of Control as Moderating Variable: Senioritas Auditor, Pengalaman Auditor Dan Keahlian Auditor Terhadap Profesional Judgment Dengan Locus of Control Sebagai Variabel Moderasi - Fajrin Noho; Sabaruddin; Sulhendri (Journal of Accounting Science, 2021)
The purpose of this research is to see the effect of auditor seniority, experience, expertise of auditors on professional judgment with locus of control as a moderating variable (a case study of the DKI Jakarta area public accounting firm). The research method used is quantitative research with a survey research form. The research technique in this study used a survey method, which aims to collect information from respondents using a questionnaire containing a list of statements submitted directly to the respondent. Data analysis in this study used the Partial Least Square (PLS) method. PLS can be used in any type of data (nominal, ordinal, interval, ratio) as well as less rigid and more flexible assumption requirements. The results of this study indicate that auditor seniority has no significant effect on professional judgment, but auditor experience and auditor expertise have a significant effect on professional judgment, whereas Locus of Control is unable to moderate the effect of auditor seniority, auditor experience, auditor expertise on professional judgment.